(untitled) (International Journal of Engineering and Computer Science, 2024)
This paper addresses the critical need for a revised systems engineering framework to ensure the safety and security of LiDAR perception software in autonomous vehicles. Traditional approaches, often rooted in waterfall methodologies, prove inadequate in addressing the complexity, stringent safety requirements (ISO 26262), and evolving cybersecurity threats inherent in this rapidly advancing field. We propose a novel framework that integrates best practices from Model-Based Systems Engineering (MBSE), agile development, formal methods, and security-by-design principles, creating a holistic approach to development and validation. This framework directly tackles the limitations of traditional methods by incorporating iterative development cycles, rigorous verification and validation processes, and proactive security measures throughout the entire lifecycle. The framework’s practical application is demonstrated through a comparative case study analyzing DBSCAN and Euclidean clustering algorithms for object detection within a safety-critical Autonomous Emergency Braking (AEB) system. This case study highlights the importance of algorithm selection, parameter optimization, and the crucial role of testing methodologies in achieving both high performance and compliance with ISO 26262 safety standards. Our analysis reveals significant performance differences between the algorithms, underscoring the necessity of a rigorous and data-driven approach to algorithm selection and validation within a comprehensive systems engineering framework. The research concludes by outlining key areas for future investigation, including advancements in algorithmic efficiency, robust sensor fusion strategies, enhanced cybersecurity measures (addressing both known and emerging threats), and the development of standardized testing and validation procedures to ensure the continued improvement and widespread adoption of safe and reliable autonomous driving systems. This holistic framework offers a significant contribution to the ongoing effort of building more robust and trustworthy autonomous vehicles, directly addressing the challenges of safety, security, and reliability in this rapidly evolving technology.